2016
DOI: 10.1111/mmi.13375
|View full text |Cite
|
Sign up to set email alerts
|

Conditional gene deletion with DiCre demonstrates an essential role for CRK3 in Leishmania mexicana cell cycle regulation

Abstract: Summary Leishmania mexicana has a large family of cyclin‐dependent kinases (CDKs) that reflect the complex interplay between cell cycle and life cycle progression. Evidence from previous studies indicated that Cdc2‐related kinase 3 (CRK3) in complex with the cyclin CYC6 is a functional homologue of the major cell cycle regulator CDK1, yet definitive genetic evidence for an essential role in parasite proliferation is lacking. To address this, we have implemented an inducible gene deletion system based on a dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 40 publications
3
76
0
Order By: Relevance
“…Using qPCR, we then examined the CRK3 excision rates after induction and showed that the CRK3 loss was achieved at 90% from D2 post induction onwards; yet the excision was never completely achieved and around 10% of the floxed gene copies persisted in the cell population (Figure 3c). These data correlate with those of Duncan et al, , where a slight amount of CRK3 protein remained detectable after induction. The growth rate of [ CRK3 Flox Puro‐Neo] and [ CRK3‐HA Flox Puro‐Neo] was assessed during 8 days after induction (Figures 3d and S2c, respectively), and a severe growth defect was observed in induced cells compared with non‐induced control cells as early as D2.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Using qPCR, we then examined the CRK3 excision rates after induction and showed that the CRK3 loss was achieved at 90% from D2 post induction onwards; yet the excision was never completely achieved and around 10% of the floxed gene copies persisted in the cell population (Figure 3c). These data correlate with those of Duncan et al, , where a slight amount of CRK3 protein remained detectable after induction. The growth rate of [ CRK3 Flox Puro‐Neo] and [ CRK3‐HA Flox Puro‐Neo] was assessed during 8 days after induction (Figures 3d and S2c, respectively), and a severe growth defect was observed in induced cells compared with non‐induced control cells as early as D2.…”
Section: Resultssupporting
confidence: 91%
“…As a proof of concept of the Floxed gene strategy, we first conditionally deleted the cyclin‐related kinase 3 ( CRK3 ) gene (Figure ), which has previously been characterised as an essential gene in L. mexicana (Duncan et al, ; Hassan, Fergusson, Grant, & Mottram, ). We transfected the L. mexicana Di‐Cre‐Cas9 cell line with PCR products containing the sgRNA and the donor DNA with or without an HA tag (see Section 3) to generate the cell lines [ CRK3 Flox Puro‐Neo] and [ CRK3‐HA Flox Puro‐Neo], respectively (Figures and S2b,c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deletion of the GOI was induced by rapamycin-mediated DiCre activation, as previously reported (82,83).…”
Section: Dna Constructs and Cell Line Generation A Background Cell Lsupporting
confidence: 77%